The second letter to the Corinthians - Bultmann, Rudolph Karl, 1884-1976; Dinkler, Erich, 1909-; Harrisville, Roy A. (Minneapolis, MN Augsburg, 1985)
Includes bibliographical references and indexes.
Originally published in German as "Der zweite Brief an die Korinther".
Keywords: Bible. N.T. Corinthians, 2nd -- commentaries